Renin-angiotensin system: The underlying mechanisms and promising therapeutical target for depression and anxiety - Gong, Sizhu; Deng, Fang (Frontiers in Immunology, 2023)
Emotional disorders, including depression and anxiety, contribute considerably to morbidity across the world. Depression is a serious condition and is projected to be the top contributor to the global burden of disease by 2030. The role of the renin-angiotensin system (RAS) in hypertension and emotional disorders is well established. Evidence points to an association between elevated RAS activity and depression and anxiety, partly through the induction of neuroinflammation, stress, and oxidative stress. Therefore, blocking the RAS provides a theoretical basis for future treatment of anxiety and depression. The evidence for the positive effects of RAS blockers on depression and anxiety is reviewed, aiming to provide a promising target for novel anxiolytic and antidepressant medications and/or for improving the efficacy of currently available medications used for the treatment of anxiety and depression, which independent of blood pressure management.